Tracheal suture in rats with hypothyroidism: wound healing study - Zimmermann,Elise (2009)
PURPOSE: To evaluate the influence of hypothyroidism in tracheal wound healing process. METHODS: A controlled study was designed with 48 male Wistar rats, divided into two groups: study and control groups. In the first one hypothyroidism was surgically induced and 10 weeks after, a tracheal opening followed by suture was performed in both groups, subdivided into 7, 14, and 21 days in accordance with the date of animals death. A laboratorial evaluation was performed to prove the decreased in thyroid function in the study group. Also a macroscopic evaluation through a stablished protocol and a microscopic analysis with Hematoxylin-eosin and Sirius-Red staining methods were done. RESULTS: The laboratorial evaluation certified suppressed thyroid function in the study group. The macroscopic evaluation showed the presence of suture blockade in the study group in all the evaluated days. Microscopic analysis showed a prolongated inflammatory process and less collagen with delay in organization in the study group comparing to control group. All these data were statistic significant. CONCLUSION: Hypothyroidism had an influence in tracheal wound healing process, promoting delay in the inflammatory and organization processes and diminished tissue collagen quantity.